Stored Grain Pack Factors for Wheat: Comparison of Three Methods to Field Measurements - Boac, Josephine M.; Bhadra, Rumela; Casada Mark E.; Thompson Sidney A.; Turner Aaron P.; Montross Michael D.; McNeill Samuel G.; Maghirang Ronaldo G. (Transactions of the ASABE, 2015)
Storing grain in bulk storage units results in grain packing from overbearing pressure, which increases grain bulk density and storage unit capacity. This study compared pack factors of hard red winter (HRW) wheat in vertical storage bins using different methods: the existing packing model (WPACKING), the USDA Risk Management Agency (RMA) method, and the USDA Farm Service Agency Warehouse Licensing and Examination Division (FSA-W) method. Grain bins containing HRW wheat were measured in Kansas, Oklahoma, and Texas. Packing was measured in corrugated steel bins and reinforced concrete bins with diameters ranging from 4.6 to 31.9 m (15.0 to 104.6 ft) and equivalent level grain heights ranging from 4.1 to 41.6 m (13.4 to 136.6 ft). The predicted masses of compacted stored wheat based on WPACKING, RMA, and FSA-W were compared to the reported mass from scale tickets. Pack factors predicted by WPACKING ranged from 0.929 to 1.073 for steel bins and from 0.986 to 1.077 for concrete bins. Pack factors predicted by the RMA method ranged from 0.991 to 1.157 for steel bins and from 0.993 to 1.099 for concrete bins. Pack factors predicted by the FSA-W method ranged from 0.985 to 1.126 for steel bins and from 1.012 to 1.101 for concrete bins. The average absolute and median differences between the WPACKING-predicted mass and reported mass were 1.64% and -1.26%, respectively, for corrugated steel bins and 3.75% and 2.16%, respectively, for concrete bins. In most cases, WPACKING underpredicted the mass in corrugated steel bins and overpredicted the mass in concrete bins. Comparison of the RMA-predicted mass and reported mass showed an average absolute difference of 4.41% with a median difference of 1.91% for HRW wheat in steel bins and an average absolute difference of 3.25% with a median difference of 1.03% for concrete bins. For the FSA-W-predicted mass versus reported mass, the average absolute and median differences were 3.40% and 3.86%, respectively, for steel bins and 4.34% and 3.50%, respectively, for concrete bins. Most of the mass values were overpredicted by both the RMA and FSA-W methods. Some of the large differences observed for concrete bins can be attributed to the unique geometry of these bins and the difficulty in describing these bin shapes mathematically. Overall, compared to the reported mass, WPACKING predicted the mass of grain in the bins with less error than the current RMA and FSA-W methods. Some of the differences may be because the RMA and FSA-W methods do not include the effects of grain moisture content, bin wall type, and grain height on pack factors.
Keywords: Commercial bin measurement; Steel and concrete bins; Stored grain pack factor; Wheat; WPACKING